Traveling light modern meditations on St Paul's letter of freedom - Peterson, Eugene H., 1932- (Colorado Springs, CO Helmers and Howard, 1988)
Includes bibliographical references.
Keywords: Bible. N.T. Galatians -- criticism, interpretation, etc